(The Role of Children’s TV Channels in the Demolition of Moral Values: Cartoon Network Arabia Channel as a Model (Analytical Study - Badr, Mostafa Akram (Arab Journal for Sciences and Research Publishing, 2018)
This study which is categorized among the Impacts of Mass Media studies, aimed to measure the amount of the disrupting content of moral values of children in the children’s television programs broadcasted on Cartoon Network Arabia Channel. The study relied on the Descriptive Analytical Method using the Content Analysis, was applied on a targeted sample from the channel’s programs, and the results revealed that the 134 TV scene sample had a repetition of 99 scene that contains disruption of children’s moral values with a rate of %73.9 of all scenes. The study also presented some proposals and recommendations to protect children’s behavior and save their moral values.
Keywords: Children's programs; animation; television; the influence of media; moral values